Implementation of a screening, brief intervention and referral to treatment programme for risky substance use in South African emergency centres: A mixed methods evaluation study - Van Der Westhuizen, C.; Myers-Franchi, Bronwyn; Malan, M.; Naledi, T.; Roelofse, M.; Stein, D.J.; Lahri, S.; Sorsdahl, K. (PUBLIC LIBRARY SCIENCE, 2019)
Background: Screening, brief intervention, and referral to treatment (SBIRT) for risky substance use is infrequently included in routine healthcare in low-resourced settings. A SBIRT programme, adopted by the Western Cape provincial government within an alcohol harm reduction strategy, employed various implementation strategies executed by a diverse team to translate an evidence-based intervention into services at three demonstration sites before broader programme scale-up. This paper evaluates the implementation of this programme delivered by facility-based counsellors in South African emergency centres.